The use of palm oil-basedwaste cooking oil to enhance the production of polyhydroxybutyrate [P(3HB)] by cupriavidus necator H16 strain - Kamilah, Hanisah; Al-Gheethi, Adel; Yang, Tajul Aris; Sudesh, Kumar (Springer, 2018)
Waste cooking oil (WCO) is of increasing interest as an inexpensive feedstock to produce biodegradable plastic, poly(3- hydroxybutyrate) [P(3HB)]. In the present study, palm oil-basedWCO(PO-WCO) was obtained from nine different locations. Palm oil-based fresh cooking oil (PO-FCO) and PO-WCO were characterised via proximate and physicochemical analysis, prior to being used as carbon sources for the biosynthesis of P(3HB) using Cupriavidus necator H16. It was shown that the free fatty acid, peroxide value, and saturated compounds in all batches of PO-WCO were higher compared to those in the PO-FCO. The cells produced 60–80 wt% P(3HB) with dry cell weight of 14–17 g/L. The weight average molecular weight (Mw) was found to be 1.8 × 106 Da with a polydispersity (Mw/Mn) of 2.7 when PO-WCO was used as the carbon source. The PO-WCO was found to be suitable to be used as a sustainable carbon source for cell growth and P(3HB) biosynthesis.